Breast cancer circulating tumor cells - Maria Joao Carvalho; Mafalda Laranjo; Margarida Abrantes; Antonio S. Cabrita; Filomena Botelho; Carlos F. de Oliveira (Oncology Reviews, 2011)
Metastasization of breast cancer involves various mechanisms responsible for progression from invasive lesion to dissemination in distant organs. Regional lymph node metastasization was considered an initial step in this process, but it is now recognized that hematogenous dissemination is a deviation from lymphatic circulation. The detection of circulating tumor cells (CTC) is an aim in several oncology areas. For this purpose, several techniques have been used to detect CTC, including the use of antibodies and techniques with nucleic acids. This study reviews the published studies considering the detection of breast cancer CTC. There are focused the difficulties in identifying a CTC in a heterogeneous population, the handling of the sample, criteria of positivity, analytical techniques, and specific markers. There are systematized various specific markers of breast cancer cells also the problems with false positive results. Finally, we hypothesize clinical applications either as a prognostic marker or as a therapeutic response monitor.